PUNCTUATION FORMS IN ENGLISH - Aliyah Fidiani; Rosanti (Cemara Education and Science, 2024)
A pause or signal used to make our sentences more clear is called punctuation.They serve as cuesto the reader to halt, emphasize a point, switch up the flow of the text, or show connections betweendifferent parts of the text. When writing, punctuation is a crucial tool that authors employ to make theirpoints concise and easy to understand. The most common punctuation marks used in writing have beencovered in this study along with examples. This research aims to give a concise summary of variousfindings that the author has looked up from multiple sources, as well as to pinpoint the most challengingpunctuation patterns in English writing and provide a number of punctuation marks that are frequentlyused in books, articles, and other written works.